Exploring Political Trust: A Bibliometric Study on the Evolution and Perspectives in Political Psychology - Faradila Umaiya; Novi Qonitatin (Proceedings of the 1st International Conference on Social Science (ICSS), 2025)
Political trust is defined as the support of citizens for political institutions, reflecting their confidence in the actions and policies of the government. This study aims to examine the research trends on political trust, particularly in the field of psychology. The research method used is bibliometric analysis with SCOPUS database, using "political trust" as the main keyword. there were 1088 documents. The final stage is to analyze the data obtained from SCOPUS The analysis is conducted using VOSviewer. The bibliometric analysis includes document types, authorship, institutions, growth trends, and future research directions. Four clusters have been identified, illustrating that political trust is related to political participation, perceptions, personality, and religion. Future research is expected to consider the findings of this study for further investigation.